Analisis Pemberdayaan UMKM dalam Perspektif Ekonomi Syariah untuk Mencapai Kesejahteraan Masyarakat - Jasri, Jasri; Mustamin, Sitti Walida; Nurmayanti, Sri (Jurnal Penelitian UPR, 2023)
This research aims to identify the role of Micro, Small, and Medium Enterprises (MSMEs) in enhancing societal well-being through the perspective of Islamic economics. The study is focused on the case of culinary businesses in the city of Makassar. The research methodology employed is a qualitative approach with descriptive characteristics, emphasizing analysis through a case study approach. The findings of the study reveal that the empowerment of MSMEs in Makassar has the capacity to improve the welfare of the community. From the standpoint of Islamic economics, these efforts of MSME empowerment are a form of implementing the principles of sharia that emphasize a prosperous life, free from various forms of hardship, both material and spiritual. The liberation of individuals from challenging circumstances is a concrete manifestation of the concept of well-being. Thus, it can be concluded that these endeavors to empower MSMEs genuinely embody the principles of sharia economics.